GE_GERICHTE P/11895/2020 vom 23. Juni 2023 - GE Cour de justice (2023)
MEURTRE;TENTATIVE(DROIT PÉNAL);LÉSION CORPORELLE;VIOLATION DU DEVOIR D'ASSISTANCE OU D'ÉDUCATION;VOIES DE FAIT;EXPULSION(DROIT PÉNAL) | CP.111; CP.22; CP.66A; CP.123.ch2; CP.180; CP.126; CP.219